2022-RA-891-ESGO Preoperative assessment of non-resectability in patients with ovarian cancer using imaging (ISAAC study) – an interim analysis. (20th October 2022) - Pinto, Patrícia; Chiappa, Valentina; Alcazar, Juan Luiz; Franchi, Dorella; Testa, Antonia Carla; Valentin, Lil; Cibula, David; Fischerová, Daniela
Abstract : Introduction/Background: The aim of the European multicentric prospective study (ISAAC study, Imaging Study on Advanced ovArian cancer) was to test the non-inferiority of abdomino-pelvic ultrasound compared to computed tomography (CT) and whole-body diffusion-weighted magnetic resonance imaging (WB-DWI/MRI) in prediction of surgical outcome in patients with ovarian/tubal/peritoneal cancer. Methodology: All consecutive patients, with suspected ovarian cancer planned for surgery underwent preoperative prediction of non-resectability with ultrasound, CT and WB-DWI/MRI at 5 european centres. The prediction of non-resectability was based on the European Society of Gynecologic Oncology (ESGO) criteria of non-resectability. Findings were compared to the reference standard (surgical outcome). Results: The interim analysis looked at data of the first 59 patients enrolled between 01/2020 and 07/2021. They underwent ultrasound and CT (n=59), and WB-DWI/MRI (n=50). Among them, 83% (49/59) had advanced-stage and 17% (10/59) had early-stage ovarian cancer. Diagnostic laparoscopy only was performed in 12% (7/59) of the cases. In the remaining 88% (52/59) laparotomy was performed with no residual disease at the end of surgery (R0) in 75% (39/52), residual disease ≤1 cm in 10% (5/52) and residual disease >1 cm in 15% (8/52). The ultrasound imaging was non-inferior neither to CT (p-value =0.029) nor to WB-DWI/MRI (p-value = 0.036). Regarding the prediction of resectability, ultrasound obtained the best results with an AUC of 0.85, sensitivity of 91.3% and specificity of 85.7%. CT and WB-DWI/MRI had similar results regarding AUC and sensitivity (0.79 vs 0.78 and 88.6% vs 87.5%), with lower specificity for CT (68.8% vs 86%). Conclusion: This interim analysis represents the first prospective study documenting that ultrasound is not inferior to CT and WB-DWI/MRI in predicting the non-resectability of patients with ovarian cancer. ESGO criteria are easy to apply in preoperative imaging without a need for more complex scoring system.